2018
DOI: 10.3390/ijms19030754
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle-Induced Cell Death and Potential Applications in Nanomedicine

Abstract: Cell death is crucial to human health and is related to various serious diseases. Therefore, generation of new cell death regulators is urgently needed for disease treatment. Nanoparticles (NPs) are now routinely used in a variety of fields, including consumer products and medicine. Exhibiting stability and ease of decoration, gold nanoparticles (GNPs) could be used in diagnosis and disease treatment. Upon entering the human body, GNPs contact human cells in the blood, targeting organs and the immune system. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 121 publications
(154 reference statements)
6
53
0
Order By: Relevance
“…Green synthesized of AuNPs (10 -42 nm) can induce the apoptosis activating the caspase-3 and 9 in human cervical cancer cells (Baharara et al, 2016) and the citrate-coated AuNPs (8 nm) promoted apoptosis eliciting BAX translocation and cytochrome c release in human liver (HL7702) cells (Gao et al, 2011). In agreement with literature findings (Sun et al, 2018;Vemuri et al, 2019), Au@PT cytotoxic effects elicited significant changes in survival and proliferation (AKT/PI3K and ERK pathways, respectively) as well as apoptotic process (pro-apoptotic BAX, anti-apoptotic BCL-xL, respectively) (Figure 5B). AKT and ERK activation levels were significantly reduced in the treatment with 2.5Au@PT and 5Au@PT than with control (Figures 5Ba-c), with a slight decrease after the incubation with 5Au@PT.…”
Section: Her Targeting: Evaluation Of Morphology Viability and Intrasupporting
confidence: 84%
See 2 more Smart Citations
“…Green synthesized of AuNPs (10 -42 nm) can induce the apoptosis activating the caspase-3 and 9 in human cervical cancer cells (Baharara et al, 2016) and the citrate-coated AuNPs (8 nm) promoted apoptosis eliciting BAX translocation and cytochrome c release in human liver (HL7702) cells (Gao et al, 2011). In agreement with literature findings (Sun et al, 2018;Vemuri et al, 2019), Au@PT cytotoxic effects elicited significant changes in survival and proliferation (AKT/PI3K and ERK pathways, respectively) as well as apoptotic process (pro-apoptotic BAX, anti-apoptotic BCL-xL, respectively) (Figure 5B). AKT and ERK activation levels were significantly reduced in the treatment with 2.5Au@PT and 5Au@PT than with control (Figures 5Ba-c), with a slight decrease after the incubation with 5Au@PT.…”
Section: Her Targeting: Evaluation Of Morphology Viability and Intrasupporting
confidence: 84%
“…The strategy of combining the properties of AuNPs with anticancer molecules could be the future of cancer nanomedicine (Sun et al, 2018). Chattopadhyay et al (2010) showed that Trastuzumab-PEG-AuNPs (30 nm) in combination with 300 kVp X-rays enhanced DNA double strand breaks (DSBs) in SKBR-3 cells.…”
Section: Her Targeting: Evaluation Of Morphology Viability and Intramentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies showed that AuNPs do not affect cell viabilities in several cell types [37], but some studies demonstrated their toxic effects [38,39]. The effect of AuNPs on choroid-retina endothelial cell viability is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Gold nanorods (AuNRs) have unique physicochemical properties, and are increasingly being recognized as promising materials for biomedical applications, including photothermal therapy, gene/drug delivery, imaging, and diagnostics . It has therefore become important to study the biological effects of AuNRs in order to understand both their potential risks as well as their beneficial properties . The shape, size, and surface chemistry characteristics of gold nanoparticles (AuNPs) play important roles in mediating their physiological activities .…”
mentioning
confidence: 99%